Cucurbits relay cropping for resource conservation and profit maximization in castor: Cucurbits relay cropping for resource conservation and profit maximization in castor - P VEERAMANI; V RAVICHANDIRAN; P A SARAVANAN; S MANICKAM; S R VENKATACHALAM; P ARUTCHENTHIL (Journal of Oilseeds Research, 2023)
A field experiment was conducted on sandy loamy soils during kharif seasons of 2020-21 and 2021-22 at Tapioca and Castor Research Station, Yethapur, Tamil Nadu to study the effect of Cucurbits relay cropping for resource conservation and profit maximization in castor as well as castor equivalent yield (CEY). The results of Castor-Bitter gourd recorded maximum yield of (9153 kg/ha) followed by Castor-Bottle gourd (7130 kg/ha.). Lowest cucurbits yield was recorded in Castor-Coccinia (3685 kg/ha). Relay cropping treatments significantly influenced CEY. Significantly the highest value of CEY (2472 kg ha) was recorded under Castor-Cucumber, followed by Castor-Bitter gourd recorded 2418 kg/ha.